Thermomechanical pulping (TMP) and Chemithermomechanical pulping (CTMP) of South African pine species : a comparative study - Dommisse, E. J. (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc) -- University of Stellenbosch, 1994.